Pengaruh Pembiayaan Gadai Syariah (RAHN) Terhadap Peningkatan Pendapatan Nasabah - Nurfadilah; Rafiuddin; Syarif Hidayatullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
In their business activities, many people are still usurious because people borrow money from loan sharks. Islamic pawnshop institutions should be more effective in introducing Islamic pawnshops to the public so that the objectives of the pawnshop can be carried out properly in accordance with the pawnshop motto “solving problems without problems”. So this study aims to determine the effect of Sharia Pawn Financing (Rahn) on increasing customer income. This research will be conducted at PT Pegadaian (Persero) Tawali Sharia Pawnshop Unit, Wera District, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data collection techniques are observation, interview and documentation. Data Analysis Techniques namely Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the study, it can be concluded that sharia pawn financing (rahn) has a significant role in helping customers obtain cash quickly, especially for those who need business capital in a short time. Rahn has proven to be one of the financial instruments that is practical and easily accessible to the public, especially those in the micro and small business sectors.